Evaluation of Adsorption Mechanism in Clogging of Materials Used in Drip Irrigation System - Chavan, Vishal K.; Balakrishnan, P.; Deshmukh, S. K.; Ingle, Vishal K. (Journal of Agricultural Engineering, 2014)
A laboratory study was conducted to understand the adsorption mechanism in clogging of different materials used in drip irrigation system. The adsorption characteristics of Langmuir and Freundlich equations for granules of PVC, LLDPE, silicon diaphragm (rubber button) and HDPE were analysed. The result indicated that the per cent clogging was higher for LLDPE indicating 6.9 to 11.1% from day 1 to day 15 compared to other grinded materials. The minimum per cent clogging was recorded as 1.1 to 3.0% for PVC. The adsorption study demonstrated that LLDPE is the most and PVC is the least susceptible to clogging.